Experimantal researches of the achievements of a current burdening course plates - Tegza, Іvan (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article presents the results of the experimental study of the peculiarities of the work under the calculation load of planar superstructural plates of the developed system of non-beating overlap. Great attention is paid to the construction of bearing structures prototype. The design of auxiliary equipment is described, which enabled to test the investigating U-block in conditions that imitate real resistance. The method of performing experimental research with indication of methods and means of measuring geometrical and physical parameters that characterize the stress-strain state and bearing capacity of the test plate is given. The conducted investigations enabled to determine the nature of deformation and destruction of the superstructure slabs as a separate element in the developed system of non-beating ceiling. Attention is drawn to the fact that the achievement of the bearing capacity is not accompanied by the process of destruction, but is characterized by significant movements of the supporting plots in the vertical plane